Bioactive Compounds for the Management of Hypertriglyceridemia: Evidence From Clinical Trials and Putative Action Targets - Schiano, Elisabetta; Annunziata, Giuseppe; Ciampaglia, Roberto; Iannuzzo, Fortuna; Maisto, Maria; Tenore, Gian Carlo; Novellino, Ettore (Frontiers in Nutrition, 2020)
Hypertriglyceridemia condition refers to the presence of elevated concentrations of triglycerides (TG) in the bloodstream (TG > 200 mg/dL). This lipid alteration is known to be associated with an increased risk of atherosclerosis, contributing overall to the onset of cardiovascular diseases (CVDs). Guidelines for the management of hypertriglyceridemia are based on both lifestyle intervention and pharmacological treatment, but the commonly low patients’ adherence, the medication-related costs and side effects can often limit the success of these prescriptions. For this reason, the search for natural alternative approaches to reduce plasma TG levels currently represents a hot research field. This review article summarizes the most relevant clinical trials reporting the TG-reducing effect of different food-derived bioactive compounds. Furthermore, based on the evidence obtained from in vitro studies, we provide a description and classification of the putative targets of action through which several bioactive compounds can exert a TG-lowering effect. Future research may lead to investigate the efficacy of novel nutraceutical formulations consisting in a combination of bioactive compounds which contribute to the management of plasma TG levels through different action targets.